SOCIAL CONFLICTS IN WILLIAM FAULKNER’S NOVEL LIGHT IN AUGUST - Tombiling, Lianny M.; Wuntu, Ceisy N.; Maukar, Merlin (KOMPETENSI, 2022)
This study aims to analyze the social conflict in William Faulkner’s novel. It is done to reveal the types of conflicts found in the novel and causes of conflict in this novel. In conducting this research, the research used qualitative methods. This research is classified as library research because the data collection is done by reading novels and reading several books and other references related to the topic. The data were analyzed based on the type of conflict and its causes and then presented descriptively. In other words, the researcher analyzed the data according to the topic and then present the result in a narrative. In analyzing the data, the researcher used a mimetic approach. The results of the research show that there are two categories of social conflict in the novel, namely: conflict between individuals and individuals and conflict between individuals and group